Encouraging Students to Speaks English through Daily English Program at Elementary School - Fitri Ramadani; Dwi Handayani; Yuri Widhianto; Butet Marthalina Saragih; Tedty Rohaya Tinambunan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
The ability to speak English is an important skill that needs to be developed from primary school onwards as preparation for global communication in the future. However, in reality, primary school students still face various obstacles in using English orally, such as limited vocabulary, inaccurate pronunciation, and low confidence in speaking. This community service activity aims to encourage students to be more active and confident in speaking English through the implementation of a Daily English Programme in primary schools. The method of implementation includes several stages, namely socialising the programme to the school, training and mentoring teachers in implementing English language habits, implementing the use of English in daily activities at school, and evaluating the activity through pre-tests and post-tests. The subjects of this community service activity were 28 primary school students. The results of the activity showed a significant improvement in the students' English speaking skills, as indicated by an increase in the average score from 47.6 on the pre-test to 73.5 on the post-test. In addition to the improvement in test results, the students also showed positive developments in terms of their courage to speak, active participation in activities, and confidence in using English. Thus, the Daily English Programme is considered effective as an effort to create a communicative learning environment and support the continuous improvement of elementary school students' English speaking skills.